Different effects of visual occlusion on interpersonal coordination of head and body movements during dyadic conversations - Kodama, Kentaro; Shimizu, Daichi; Fujiwara, Ken (Frontiers in Psychology, 2024)
In recent decades, interpersonal coordination and synchrony have been extensively examined in the field of psychology and cognitive science. Studies suggest that perceptual information enables interpersonal coordination and that perceptual noise may even enhance coordination. However, how these perceptual factors influence interpersonal coordination dynamics between head and body movements remains unclear. This study investigated the effect of visual information on the interpersonal coordination of head and body movements during dyadic conversations. Methods: The availability of visual information was manipulated by positioning a partition halfway between a pair of participants, and the conversations were recorded using a video camera. A video-based human pose estimation software (OpenPose) was used to quantify each interlocutor's head and body movements, which were submitted for cross-recurrence quantification analysis (CRQA), to assess the degree of coordination between the interlocutors. Results: The results showed different effects between head-and body-movement coordination (i.e., a CRQA measure, maximum line length). The occlusion of visual information increased head-movement coordination, whereas it decreased body-movement coordination. Discussion: The results suggest that a distinct mechanism may be present at the head-and body-movement coordination level and this study observed differing appearances of compensatory behaviors. Further studies should be conducted to investigate the complex relationships between interpersonal coordination dynamics and various kinds of communication constraints, such as long-term or short-term, and lower-order (perceptual-motor) or higher-order (cognitive-social) level constraints.